PENGARUH PROFITABILITAS, LIKUIDITAS, DAN SOLVABILITAS TERHADAP NILAI PERUSAHAAN PADA SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2019-2023 - Sarmila Rumaf; Abdul; Agus Sumarnadi (PUTRA JAWA PUBLISHER, 2025)
This study aims to examine the effect of profitability (ROA), liquidity (CR), and solvency (DER) on firm value as measured by Price to Book Value (PBV) in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The research method used is quantitative with an associative approach. The data were obtained from the companies’ annual financial statements and analyzed using classical assumption tests (normality, multicollinearity, and heteroscedasticity), multiple linear regression, t-test (partial), F-test (simultaneous), and coefficient of determination (R²) processed with IBM SPSS version 23. The results show that profitability (ROA) has a significant effect on the logarithm of firm value, indicating that higher profitability leads to a higher firm value. In contrast, liquidity (CR) and solvency (DER) have no significant effect on firm value, suggesting that liquidity conditions and funding structure are not the main factors influencing firm value in the energy sector during the study period. Furthermore, the F-test results indicate that ROA, CR, and DER jointly have a significant effect on firm value, confirming that the regression model is valid in explaining the variation of firm value. These findings highlight profitability as the main consideration for investors, while liquidity and solvency still need proper management to maintain financial stability.